PERBEDAAN PERMAINAN ORIGAMI DAN MEWARNAI TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK PEREMPUAN PRASEKOLAH DI TK GRAND BALI BEACH SANUR - Ni Made Ameondari; Made Niko Winaya; Luh Made Indah Sri Handari Adiputra; I Wayan Gede Sutadarma (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2016)
ABSTRACTIncrease motor development can be done by providing a stimulus. Good stimulus will stimulate children's development in various aspects. With the aim to know the difference between origami and coloring in improving fine motor development of children. Draft Pre and Post Test Two Group Design. Sampling using simple random sampling. These samples included 32 people and data collection is done with Fine Motor Skills Tests. The results showed an increase fine motor development in group 1 amounted to 70.31±3.754 and in group 2 an increase of 71.44±5.046. Independent Sample test showed no significant difference between group 1 and 2 p = 0.894 (p> 0.05). It was concluded that the origami and coloring equally well to improving fine motor development of children. Keywords : Fine motor, origami, coloring.